The Williams syndrome prosociality gene GTF2I mediates oxytocin reactivity and social anxiety in a healthy population. (30th April 2017) - Procyshyn, Tanya L.; Spence, Jason; Read, Silven; Watson, Neil V.; Crespi, Bernard J.
Abstract : The neurohormone oxytocin plays a central role in human social behaviour and cognition, and oxytocin dysregulation may contribute to psychiatric disorders. However, genetic factors influencing individual variation in the oxytocinergic system remain poorly understood. We genotyped 169 healthy adults for a functional polymorphism in GTF2I ( general transcription factor II-I ), a gene associated with high prosociality and reduced social anxiety in Williams syndrome, a condition reported to involve high oxytocin levels and reactivity. Participants' salivary oxytocin levels were measured before and after watching a validated empathy-inducing video. Oxytocin reactivity, defined as pre- to post-video percentage change in salivary oxytocin, varied substantially and significantly between individuals with different GTF2I genotypes, with, additionally, a trend towards an interaction between genotype and sex. Individuals with more oxytocin-reactive genotypes also reported significantly lower social anxiety. These findings suggest a model whereby GTF2I has a continuum of effects on human sociality, from the extreme social phenotypes and oxytocin dysregulation associated with gene deletion in Williams syndrome, to individual differences in oxytocin reactivity and sociality associated with common polymorphisms in healthy populations.